Removal of Cu (II) and Zn (II) from water with natural adsorbents from cassava agroindustry residues - Schwantes, Daniel (2015)
Current study employs solid residues from the processing industry of the cassava (Manihot esculenta Crantz) (bark, bagasse and bark + bagasse) as natural adsorbents for the removal of metal ions Cu(II) and Zn(II) from contaminated water. The first stage comprised surface morphological characterization (SEM), determination of functional groups (IR), point of zero charge and the composition of naturally existent minerals in the biomass. Further, tests were carried out to evaluate the sorption process by kinetic, equilibrium and thermodynamic studies. The adsorbents showed a surface with favorable adsorption characteristics, with adsorption sites possibly derived from lignin, cellulose and hemicellulose. The dynamic equilibrium time for adsorption was 60 min. Results followed pseudo-second-order, Langmuir and Dubinin-Radushkevich models, suggesting a chemisorption monolayer. The thermodynamic parameters suggested that the biosorption process of Cu and Zn was endothermic, spontaneous or independent according to conditions. Results showed that the studied materials were potential biosorbents in the decontamination of water contaminated by Cu(II) and Zn(II). Thus, the above practice complements the final stages of the cassava production chain of cassava, with a new disposal of solid residues from the cassava agroindustry activity.